Polymer-Modified Liquid Crystals 2019
DOI: 10.1039/9781788013321-00045
|View full text |Cite
|
Sign up to set email alerts
|

Electron Beam Curing of Monomer/Liquid Crystal Blends

Abstract: This chapter focuses on a comparison of two polymerization/crosslinking methods to produce polymer/liquid crystal (LC) systems: rapid UV-visible irradiation and high voltage accelerated electron beams (EB), with comparable exposure times. The comparison was performed in terms of some physical properties such as phase diagrams, polymerization and phase separation kinetics, morphologies, and electro-optical responses. During polymerization and crosslinking, the longer the spacing between the two acrylic double b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…By making a suitable choice of components of the mixture, it is possible to obtain a transparent film when the system is subjected to a sufficient electric voltage ("on" state) and opaque in the absence of voltage ("off" state). These materials are of interest for their many applications, especially in the field of electroactive glazing and display devices [31][32][33][34].…”
Section: (B) Their Use In Pdlc Systemsmentioning
confidence: 99%
“…By making a suitable choice of components of the mixture, it is possible to obtain a transparent film when the system is subjected to a sufficient electric voltage ("on" state) and opaque in the absence of voltage ("off" state). These materials are of interest for their many applications, especially in the field of electroactive glazing and display devices [31][32][33][34].…”
Section: (B) Their Use In Pdlc Systemsmentioning
confidence: 99%
“…The effects of both radiation dose and dose rate on the preparation of UV-and EBcured polymer and polymer/LC films were investigated by Bouchakour et al [12,13] on TPGDA/E7 and other similar acrylic systems. Polymerization and crosslinking reactions of monomer/LC mixtures may introduce phase separation processes that are likely to govern sample morphologies of the obtained polymer/LC films.…”
Section: Development Of Crosslinked Polymer/lc Filmsmentioning
confidence: 99%
“…In particular, the decrease in the FTIR-bands associated with the carbon-carbon double bonds of the acrylate groups were followed (C=C deformation band at 810 cm −1 , and another C=C valence vibration around 1638 cm −1 ), as a function of a radiation dose. It was found that increasing the radiation doses lead to an increase in the acrylic double bond conversion [13]. The LC E7 acts as a solvent and the polymerization reaction was governed by the diffusion of the initiator radicals in this solvent towards the acrylic double bonds.…”
Section: Development Of Crosslinked Polymer/lc Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three acrylic polypropylene glycol diacrylate (PPGDA) monomers were used, with reactive chains of different molecular weights between their two acrylic end groups. These materials were chosen because they have already been studied in the UMET laboratory and present interesting electro-optical, thermophysical, and mechanical properties [26][27][28].…”
Section: Introductionmentioning
confidence: 99%